PERBAIKAN SISTEM OPERASIONAL USAHA TRAVEL SEBAGAI UPAYA PENINGKATAN KUALITAS MANAJEMEN - Azhari, Azhari; Moh. Mustofa; Muslinawati, Retno; Dwi Meisari, Erika; Setia Anggarista, Erika Tri (Universitas Kadiri, 2024)
Activity Aims To Improve The Travel Business Operational System As An Effort To Improve Management Quality Based on the results of assistance for the